2D transition metal dichalcogenide nanomaterial-based miRNA biosensors. (June 2021) - Mitrevska, Katerina; Milosavljevic, Vedran; Gagic, Milica; Richtera, Lukas; Adam, Vojtech
Highlights: Comprehensive review of 2D nanomaterial-based miRNA biosensors. Review of emerging microRNAs biomarkers and their detection. Discussion of the biosensor designs based 2D transition metal dichalcogenide nanomaterial. Highlight of miniaturization and future perspectives. Abstract: MicroRNAs (miRNAs) are short oligonucleotides responsible for the regulation of basic cellular mechanisms. The detection of miRNA in clinical practice involves conventional methods (northern blot, microarrays, RT-qPCR) that provide good sensitivity and specificity. However, their high cost and time-consuming nature prevent their implementation as routine analysis. Biosensors, as alternative detection platforms, can compensate for these flaws, providing good sensitivity and specificity as well as low prices per assay and fast generation of results; therefore, biosensors may ultimately replace conventional methods. The fast progress in nanotechnology has created new prospects in biosensor fabrication, presenting a selection of nanomaterials compatible for the detection of various biomolecules. Two-dimensional transition metal dichalcogenides (2D TMDCs) demonstrate promising qualities, such as biocompatibility, a large surface area for detection and diverse possibilities for altering electrochemical and optical properties; hence, an improved detection performance can be achieved. In this review, the recent progress in biosensor fabrication for detecting miRNAs based on 2D TMDCs is summarized and supported by the basic understanding of miRNA biosynthetic pathways and detection methods. Additionally, insight into the structure and properties of TMDCs will be disclosed as well as suitable methods for their synthesis and the mechanisms for tuning their properties. Graphical abstract: Image, graphical abstract